Kelimpahan dan Potensi Biofuel Mikrofitobenthos dari Perairan Sungai Pekacangan yang terkena Limbah Cair Tapioka - Christiani Christiani; A Ilalqisny Insan; Dwi Sunu Widyartini (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Microphytobenthic a benthic plants, found in the waters of the sunlight reaching the bottom waters. In addition to acting as a primary producer also has the potential to produce renewable biofuels The purpose of this study was to determine the microphyitobenthic abundance of river Pekacangan affected tapioca liquid industrial waste and to estimate its potential as a biofuels. This research used survey method with the sampling technique is purposive sampling based on existing environmental setting. As the main parameters are the types of microphytobenthic, while supporting research parameters are temperature, light penetration, pH, dissolved O2, BOD5, current velocity, TSS, TDS, nitrate, orthophosphate and silica. Microphytobenthic obtained at stations affected by the waste, in screening to determine its oil content.Abundance of microphytobenthic at a station directly exposed tapioca liquid waste 620 ind.mm-2.Isolated microphytobenthic River Pekacangan affected tapioca liquid waste had 22 isolates of microphytobenthos and after screened allegedly 7 isolates potential as a biofuel, namely Navicula sp., Amphora libyca, Ulothrix sp., Anabaena sp., Planctonema sp., Cymbella sp., and Eunotia sp.